Production Of Ginger- And Aloe Vera-Based Herbal Wines And Their Antimicrobial Profiling (Applied Biological Research, 2023)
Herbal wines are rich decoction of active secondary metabolites of plants. The  consumption of herbal wines imparts health benefits to the consumers because  of their antioxidant and antimicrobial properties. In light of the increasing  demand for value-added herbal products, the present study aimed to develop a production process for herbal wine from aloe vera and ginger juices. The  prepared herbal wines were evaluated for their antimicrobial properties against  food-borne pathogens. Aloe vera and ginger juices were adjusted to TSS level of  20° Brix by adding honey. The juices were subjected to fermentation using an  active culture of Saccharomyces cerevisiae at 28°C. Various fermentation  parameters like pH, TSS, reducing sugars, and ethanol concentrations were  periodically measured. The wine samples were analysed for titratable acidity,  total phenolic content, and antimicrobial potential by standard methods. The  aloe-vera and ginger wines showed final titratable acidity of 0.09 and 0.16; a ºBrix to acid ratio of 66.6 and 56.2, respectively, in a fermentation period of 20  days. Total phenolic content was 34.5 ± 0.28 for aloe vera wine and 179.6 ± 0.56  for ginger wine. The alcohol content of aloe vera and ginger wine was 8.29 and  7.91 with fermentation efficiency of 97.8 and 96.2, respectively. Both herbal  wines exhibited antimicrobial activity against food-borne pathogens, E. coli and Bacillus cereus. These wines can be accepted as safe and healthy drinks as they  retained good phytochemical characteristics.
Keywords: Aloe vera; foodborne pathogens; ginger; herbal wine